ANALISIS PENGUNGKAPAN (DISCLOSURE) LAPORAN KEUANGAN KABUPATEN YANG MERAIH OPINI AUDIT WAJAR TANPA PENGECUALIAN (WTP) DUA TAHUN BERTURUT-TURUT - Haryadi, Eko Susilo; Ratnawati, Vince (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
The purpose of this research is to analyze and decrypt that disclosure is one of theconsiderations giving CPC opinion on Local Government Finance Report (LKPD) In2013 Regency and Regency Kuantan Meranti Islands Singingi in Riau Province.CPC Examination Report on the Financial Statements Meranti Islands Districtobtains Unqualified Opinion (WTP) 2 (two) years in a row and Regency KuantanSingingi obtain Unqualified Opinion (WTP) three (3) consecutive years. Thisresearch is a descriptive study using quantitative data types and qualitative data.This study uses primary data and secondary data as a source of data collectedusing the research documents, then analyzed using content analysis (contentanalysis). Based on the conclusion, that the disclosure (disclosure) which isconducted by the District WTP opinion that won two consecutive years has met thefull disclosure as set forth in the statement number 01 Government Regulation No.71 of 2010 concerning the Government Accounting Standards. Then theresearchers compared the completeness of the disclosure by the Local GovernmentOpinion WDP indeed obtain different levels of completeness of disclosure. However,giving opinions are not only influenced by the disclosure, but there are otherconsiderations that are used by the auditor.Keywords: Disclosures and unqualified opinion